Pengaruh Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return on Assets, Loan To Deposit Ratio, dan Bank Size terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Aries Santoso; Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
This study aims to analyze the influence of Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return on Assets, Loan to Deposit Ratio, and Bank Size jointly and partially to Stock Price of banking sector company that listed on Indonesian Stock Exchange for period 2011-2018. This research used the purposive sampling method and obtained the 5 largest market capital banking sector companies as a sample. The analysis method used is multiple linear regression through SPSS 26 program. The results of this study show that Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return On Assets, Loan to Deposit Ratio, and Bank Size have significant influence to stock price. While Capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio partially have significant influence on the stock price. Meanwhile, Net Interest Margin, Return On Asset, and Bank Size have not a significant influence on the stock price of banking sector company that listed on the Indonesian Stock Exchange for period 2011-2018. Penelitian ini dimaksudkan untuk mencari pengaruh Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return On Assets, Loan to Deposit Ratio, dan Bank Size mengenai keterkaitannya pada harga saham baik secara bersamaan maupun parsial terhadap harga saham perusahaan sektor bank yang ada di Bursa Efek Indonesia untuk periode penelitian 2011 – 2018. Penelitian ini mengunakan metode purposive sampling yang ditetapkan sebanyak 5 perusahaan sektor perbankan yang memiliki kapitalisasi pasar terbesar sebagai sampel. Metode analisis yang dipakai menggunakan regresi linear berganda melalui bantuan SPSS 26. Hasil penelitian membuktikan secara simultan, Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return On Assets, Loan to Deposit Ratio, dan Bank Size berpengaruh signifikan terhadap harga saham. Sementara secara parsial, Capital Adequacy Ratio, Non-Performing Loan, dan Loan to Deposit Ratio berpengaruh terhadap harga saham. Sedangkan Net Interest Margin, Return On Asset, dan Bank Size tidak berkaitan terhadap harga saham sektor bank yang terdaftar di Bursa Efek Indonesia periode 2011-2018.